Comportement d'un pergélisol expérimental soumis à un réchauffement - Hurault, B. (HAL CCSD, 2011)
The goal of this work was providing experimental data to better constrain the impact of global warming on permafrost. Methodology was based on physical modeling in a cold room. This allows identifying and defining the evolution processes of the experimental permafrost. Experimental permafrost was built-up based on available field data. The lithology of the material used was a mixture of fine sand and loam from the plain of Caen. Ice content is between 30 and 80%. Models are not scaled and dimensional problems are not considered. Indeed, these experiments are a preliminary work. This study on the behaviour of an experimental warming permafrost allows a better understanding of (i) the changes in topography (thaw-settlement), (ii) the changes in the active layer, (iii) the thermal evolution of an experimental permafrost (freezing and thawing fronts monitoring) and (iv) the influence of different parameters (temperature, lithology, water-content, ice-content and icelayer). This work has contributed to the development of new experimental techniques and it will enhance physical modeling databases on permafrost. Ce travail a pour but d'apporter des données expérimentales pour aider à mieux contraindre l'impact du réchauffement climatique sur les pergélisols. La méthodologie utilisée est basée sur la modélisation physique en enceinte de gel qui permet d'identifier et paramétrer les processus d'évolution d'un pergélisol expérimental. Le pergélisol expérimental est reconstitué en s'appuyant sur les données de terrain disponibles. La lithologie du matériau utilisé est un mélange de sable calibré de Nemours et de limons de la plaine de Caen aux caractéristiques physiques bien définies. Les teneurs en glace sont comprises entre 30 et 80%, comme mesuré sur le terrain. Le modèle n'est pas à l'échelle 1 et les problèmes de dimensionnement ne sont pas pris en compte. En effet, cette expérimentation est un travail préliminaire. Cette étude du comportement d'un pergélisol expérimental soumis à un réchauffement a permis de mieux ...